Characterization and mapping of soil classes of the Lajeado Pessegueiro watershed in Santa Catarina, Brazil (2018)
Pedological surveys and physiographic characterization of a watershed are fundamental procedures for planning the soil use. Thus, the aim of this study was to characterize and map the soil classes of the Lajeado Pessegueiro watershed, located in Guarujá do Sul, Santa Catarina, Brazil. The types of land use and occupation, slope classes and physiography of the study area were delineated and described. Data were collected from 19 complete soil profiles and 9 extra samples. Physiographic analysis was performed using prior information on the photopedology of the terrain geomorphological characteristics, climatic conditions, vegetation, land use and geological conditions. The watershed has a predominant undulating relief (406.51 ha). The predominant land use is agricultural, with temporary annual crops (50.09%). The predominant physiography is colluvial erosional slope (35.53%), followed by erosional slope (27.13%), plateau slope (21.55%), alluvial colluvial valley bottom (10.51%) and erosional colluvial slope (5.23%). The soil classes found were Red Nitosols (37.54%), Haplic Nitosols (8.22%), Haplic Cambisols (35.20%), Fluvic Cambisols (3.92%), Red Argisols (10.09%) and Litholic Neosols (5.04%). The data showed the importance of using the physiographic analysis of the area with geoprocessing techniques, assisting pedological surveys with presentation through thematic maps. These maps serve as a base material in studies evaluating land uses, and those aiming to contribute to a better planning of soil use.